The blob that ate everyone - Stine, R. L. (New York : Scholastic, 1997)
Zackie Beauchamp wants to be a famous horror author, but even he is frightened when everything he writes on the old typewriter he found in a burned-out antique store starts to come true.
"An apple paperback."
"A Parachute Press book"--T.p. verso.
2.8
5-8.
Keywords: Authors -- Fiction; Typewriters -- Fiction; Horror stories; Authors -- Fiction; Typewriters -- Fiction; Horror fiction